ANALISIS HUBUNGAN FUNDAMENTAL DENGAN RISIKO SISTEMATIS DAN DIVIDENT PAY OUT RATIO PADA PERUSAHAAN YANG TERGABUNG DI JAKARTA ISLAMIC INDEX (JII) - Muhammad Muwidha; Mahmudatul Himmah; Andi Kusuma Indrawan (Politeknik Negeri Malang, 2022)
rity returns and risks related to investors' investment activities. The total population of 30 companies based on purposive technique with continuous listing criteria, profit and dividend payments resulted in a total sample of 15 companies. The results of the study explain that the risk of the beta company group is the company has a risk that is sensitive to the business environment. Meanwhile, dividend payments are around 45% of profit. This shows that the rate of return is quite promising. ROE in the range of 23%-27%, CR ranging from 123-221 times, DR ranging from 41%-48%, DOL ranging from 0.8% - 8.1% and for AG ranging from 7.8% - 13.84%. Both sets of variables show a close relationship with a canonical correlation value of 66.003%. This finding explains that for investment in shares of Islamic companies, the level of stock risk has a close relationship with ROE and AG. So that it will be taken into consideration in making investment decisions.